Models of individual behaviour and implications for environmental policy - Jeroen C. J. M. van den Bergh; Ada Ferrer-i-Carbonell; Giuseppe Munda (Fondazione Eni Enrico Mattei (FEEM), 1998)
Most insights of environmental economics are in line with the standard neo-classical economic model of rational behaviour, formulated in terms of maximisation of utility in general, or profits in particular. The standard theory of environmental policy is a case in point. However, the maximisation hypothesis and its methodological foundation have been criticised on many grounds, related to a lack of either logical or empirical content. Moreover, over the years great many alternative models of behaviour have been proposed. Both criticism and alternatives are surveyed here. In the context of environmental economics behavioural assumptions have been most significant for the development of economic valuation theory and environmental policy theory. The focus here will be on environmental policy theory.
Keywords: 330; Behaviour; Maximisation hypothesis; Bounded rationality; Uncertainty; Environmental regulation; Umweltökonomik; Verhaltensökonomik; Umweltpolitik; Theorie